Digital Microscopy - Sluder, Greenfield; Wolf, D. E. (David E.) (San Diego, CA : Academic Press, 2013)
This book provides the essential tools and methods for working with digital microscopy as a technique for quantitative biological research.
Microscope basics / Greenfield Sluder, Joshua J. Nordberg -- The optics of microscopic image foundation / David E. Wolf -- Proper alignment of the microscope / Rudi Rottenfusser -- Fundamentals of fluorescence and fluorescence microscopy / David E. Wolf -- Fluorescent protein applications in microscopy / Whitney L. Johnson, Aaron F. Straight -- Live-cell fluorescence imaging / Jennifer C. Waters -- Practical aspects of adjusting digital cameras / Joshua J. Nordberg, Greenfield Sluder -- Cameras for digital microscopy / Kenneth R. Spring -- A high-resolution multimode digital microscope system / Edward D. Salmon, Sidney L. Shaw, Jennifer C. Waters, Clare M. Waterman-Storer, Paul S. Maddox, Elaine Yeh, Kerry Bloom -- Electronic cameras for low-light microscopy / Ivan Rasnik, Todd French, Ken Jacobson, Keith Berland -- Camera technologies for low light imaging : overview and relative advantages / Butch Moomaw -- Post-processing for statistical image analysis in light microscopy / Richard A. Cardullo, Edward H. Hinchcliffe -- 65,000 shades of grey : use of digital image files in light microscopy / Sidney L. Shaw, Edward H. Hinchcliffe -- Quantitative analysis of digital microscope images / David E. Wolf, Champika Samarasekera, Jason R. Swedlow -- Evaluating optical aberrations using fluorescent microspheres : methods, analysis, and corrective actions / Paul C. Goodwin -- Ratio imaging : practical considerations in measuring intracellular CA2+ and pH in living cells / Nathan O'Connor, Randi B. Silver -- Quantitative fluorescence microscopy and image deconvolution / Jason R. Swedlow -- Practical aspects of quantitative confocal microscopy / John M. Murray -- Theoretical principles and practical considerations for fluorescence resonance energy transfer microscopy / Richard A. Cardullo -- Fluorescence lifetime imaging microscopy for quantitative biological imaging / Leng-Chun Chen, William R. Lloyd, III, Ching-Wei Chang, Dhruv Sud, Mary-Ann Mycek -- Fluorescence correlation spectroscopy : molecular complexing in solution and in living cells / Dylan A. Bulseco, David E. Wolf -- Breaking the resolution limit in light microscopy / Rainer Heintzmann, Gabriella Ficz -- Circumventing photodamage in live-cell microscopy / Valentin Magidson, Alexey Khodjakov -- A user's guide to localization-based super-resolution fluorescence imaging / Graham T. Dempsey -- Quantitative ratiometric imaging of FRET-biosensors in living cells / Desiree Spiering, Jose Javier Bravo-Cordero, Yasmin Moshfegh, Veronika Miskolci, Louis Hodgson -- Tip-enhanced raman spectroscopy for the base interrogation of DNA / Noah Kolodziejski.
Text in English.
Includes bibliographical references at the end of each chapters and index.
Online resource; title from title page (ebrary, viewed August 22, 2013).
Keywords: Microscopy; Image processing -- Digital techniques; Microscopy -- methods; Image Processing, Computer-Assisted -- instrumentation; Image Processing, Computer-Assisted -- methods; Microscopy -- instrumentation; Microscopy; Microscopie; Traitement d'images -- Techniques numériques.; microscopy; digital imaging; Image processing -- Digital techniques; Microscopy